(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article is one of today’s urgent problems, in which the great intellectual Ibn Sina’s idea of raising a perfect person physically and mentally is studied, and the importance of using it in the formation of positive qualities and qualities of young people is highlighted.